Increased Suicidal Ideation in Patients with Co-Occurring Bipolar Disorder and Post-Traumatic Stress Disorder. Issue 4 (2nd October 2017) - Carter, Julia M.; Arentsen, Timothy J.; Cordova, Matthew J.; Ruzek, Josef; Reiser, Robert; Suppes, Trisha; Ostacher, Michael J.
Abstract : Suicide risk increases for those with Bipolar Disorder or PTSD, however little research has focused on risk for co-occurring Bipolar Disorder and PTSD. The aim of this article was to evaluate increased suicide risk in co-occurring disorders, and differences in suicide risk for patients with Bipolar I versus Bipolar II. This study evaluated suicide risk in patients with co-occurring PTSD and Bipolar Disorder (n = 3, 158), using the MADRS and Suicide Questionnaire. Those with history of PTSD had significantly higher suicidal ideation than those without (U = 1063375.00, p < .0001). Those with Bipolar I had higher risk than those with Bipolar II. Patients with Bipolar I and PTSD were at higher risk for suicidal ideation, implying the importance of diagnosis and risk assessment.